Methyl anthranilate as generator and quencher of reactive oxygen species: a photochemical study - Gambetta, Carolina (2013)
Methyl anthranilate (MA) is a naturally occurring aromatizer and flavorant agent frequently employed in food industry and in personal care products. Due to the property of MA of being a UV-A radiation-absorber it is incorporated to topical sunscreen formulations. Within the framework of the wide variety of practical uses and applications, the photodegradation of MA becomes a topic of interest from health to an economic point of view. In this context, kinetics and mechanistic aspects of its photo-oxidation has been studied, in order to know the degradation pathways of MA under natural-like photoirradiation. The assays were performed in the absence and in the presence of riboflavin (Rf, vitamin B2) acting the later as a native photosensitizer. The results showed that MA is capable to generate singlet molecular oxygen (O2(1Δg)) upon direct UV-A irradiation, with a quantum yield value of 0.13 ± 0.02. The anthranilate also quenches the oxidative species with an overall rate constant value kt = 2.1 ± 0.2 × 107 M−1 s−1 while the reactive interaction between MA and O2(1Δg) showed a rate constant value in the range of 5.9–6.8 × 106 M−1 s−1. The kr/kt ratio, lower than 0.35 indicates that only one third of the O2(1Δg)-quenching events effectively lead to oxidation of the scavenger, being this an acceptable property for a sunscreen component. Regarding the Rf-photosensitized visible-light irradiation of MA–Rf mixtures, the anthranilate quenches the electronically excited singlet and triplet states of the vitamin. As a result the oxidative species O2− and H2O2, are generated, being the later effectively deactivated by MA. At first, the described results would show MA as a candidate for UV-A and visible-light mediated degradation. Nevertheless, at the same time MA acts as a moderate physical scavenger of photogenerated oxidative species in a sort of self-protector against photoinduced degradation and protector of oxidizable surrounding compounds.